An algorithm for the fast estimate of the maximum power voltages in PV applications adopting microconverters. Issue 1 (5th January 2015) - Ahmed Masmoudi, Dr; Balato, Marco; Vitelli, Massimo
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to discuss the main parameters influencing the performances of Distributed Maximum Power Point Tracking (DMPPT) and to present an algorithm aimed at the maximization of the energetic efficiency of the grid-connected PhotoVoltaic (PV) systems. Such an algorithm is based on the estimate of the optimal operating range of the input inverter voltage and of the optimal operating voltages of the PV modules. Design/methodology/approach – The Fast Estimate of the Maximum Power Voltages algorithm, described in this paper, is based on the idea that the controllers of the DC/DC converters (DMPPT function) and the controller of the inverter (Central MPPT function) must be able to exchange useful data in order to carry out a suitable technique based on the jointed adoption of DMPPT and CMPPT function. Such a technique is essentially based on the knowledge, even if in approximate form, of the Power vs Voltage (P-V) characteristic of a string composed by PV modules and DC/DC converters and on the consequent fast identification of a set of operating points for the inverter and for the PV modules. Findings – The main advantage of the proposed algorithm is represented by the fast identification of a set of operating points for the inverter and for the PV modules, which allows to obtain a marked increase of the speed of tracking both of the inverter and of the DC/DC converters performing the DMPPT function. Originality/value – The simulation results, shown in this paper, confirm the validity of the proposed original approach.